ANALISIS TINGKAT KEMAMPUAN SISWA DALAM MENULIS CERITA PENDEK PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD ULUMUL ISLAM BAKRI WAHID, KOTA MAKASSAR (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to analyze students' difficulties in writing short stories in the Indonesian language class IV at Ulumul Islam Bakri Wahid Elementary School. The type of research is descriptive qualitative and the data analysis techniques used are data collection, data reduction, data display and conlusion drawing. And the data source data in this study were all 4th graders of Ulumul Islam Bakri Wahid Elementary School, Makassar City. The data techniques in this study were the distribution of test sheets, student and teacher interviews and documentation in the research conducted at Ulumul Islam Bakri Wahid Elementary School.The results of this study indicate that the ability level of students in writing short stories is still low. Based on the results of writing short stories that have been made by students and the results of interviews conducted by teachers and students with researchers, it shows that the difficulties experienced by students are difficulties in expressing ideas, limited vocabulary and difficulty determining the structure of short stories so that students have difficulty in making a story. short.